Application of productive function models for providing the performance level of processing company of fat-and-oil branch of Ukraine - Blahodyr, L. M. (Visnyk of Vinnytsia Politechnical Institute, 2014)
A productive function is considered as specific statistical model, representing dependence of volume of output of products on the factors of production, and also economic sense of parameters of productive functions and their interpretation is suggested. Methodology of realization of economic analysis is expounded on the basis of productive function. The suggested methodologies of realization of economic researches are approved on the basis of data of PAO «Vinnytsia Fat-and-Oil Plant».